Increased coronary pericoronary adipose tissue attenuation in diabetic patients compared to non-diabetic controls: A propensity score matching analysis - Yu, Yarong; Ding, Xiaoying; Yu, Lihua; Dai, Xu; Wang, Yufan; Zhang, Jiayin (Journal of cardiovascular computed tomography, 2022)
Pericoronary adipose tissue (PCAT) attenuation is an indicator of active inflammation of perivascular adipose tissue, which is supposed to increase in diabetic patients. We aimed to investigate the PCAT attenuation values and high-risk plaque (HRP) features in diabetic and non-diabetic subjects with different stenotic extents. Consecutive type 2 diabetes patients and non-diabetic patients with chest pain and intermediate pre-test probability of coronary artery disease (CAD) were prospectively enrolled and underwent coronary computed tomography angiography (CCTA). At per-patient level, PCAT attenuation values of three major epicardial coronary vessels, as well as HRP features were measured. PCAT attenuation values and HRP features were compared between diabetic and non-diabetic subjects according to the presence or absence of obstructive stenosis. 1700 patients (mean age: 65.5 ​± ​11.7, 940 males) were divided into two groups according to presence of obstructive stenosis on CCTA. Propensity score matching was performed in further analysis. RCAPCAT was significantly higher in diabetic subjects than that in non-diabetic subjects, regardless of the presence of obstructive stenosis (−83.60 ​± ​9.51 HU vs. −88.58 ​± ​9.37 HU, p ​< ​0.001) or absence of obstructive stenosis (−83.70 ​± ​10.32 HU vs. −88.76 ​± ​8.28 HU, p ​< ​0.001). In contrast, HRP features were more commonly presented in diabetic patients with obstructive stenosis than in those without obstructive stenosis. According to subgroup analysis based on acquisition tube voltage, RCAPCAT was the only parameter showing consistent difference between diabetic and non-diabetic patients. RCAPCAT was significantly higher in diabetic patients than that in non-diabetic patients regardless of stenotic severity and plaque vulnerability.